-2(6-3x)=-12+6x

Simple and best practice solution for -2(6-3x)=-12+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(6-3x)=-12+6x equation:


Simplifying
-2(6 + -3x) = -12 + 6x
(6 * -2 + -3x * -2) = -12 + 6x
(-12 + 6x) = -12 + 6x

Add '12' to each side of the equation.
-12 + 12 + 6x = -12 + 12 + 6x

Combine like terms: -12 + 12 = 0
0 + 6x = -12 + 12 + 6x
6x = -12 + 12 + 6x

Combine like terms: -12 + 12 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 2m^2+15m+25=0 | | -5d=19 | | 4a-5=29-3 | | 4(9x+2)-5(3+4x)=0 | | -6+k=18 | | 14x-48=x^2 | | 6(x-3)+10=6x-8 | | 3/2-6+5/2=4t+2 | | 3x+5=7+3x-9 | | 5+1.5(z+2)=3.5z-6 | | 2r^2-r-5.25=0 | | 6+-3(6)= | | b^2+8b=-16 | | 475x+25=725 | | 3x+5=7+3y-9 | | b^2+8b=16 | | W-12=-4 | | 5x(2x-1)(5x+7)=0 | | b-6=-3 | | 5n(n+2)=10 | | 8(4-2x)=12-16x | | 2(2x-3)-5(1x+1)=x-4 | | a(a-9)(a-8)=0 | | 6(2q-1)=2q+8q | | N+3.4=5.6 | | n/5+3-10=30 | | a(bx-2)=cx+6 | | 6(4.5y)-12=9 | | (a+9)(a+2)=0 | | p+0.06p=148.4 | | n*5+3-10=30 | | 5x-5=4x+7 |

Equations solver categories